A technical visit to TNB Stesen Janakuasa Sultan Azlan Shah, Manjung - Mohammad Nazri, Mustafa, Ir. (The Instituition of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org